Investigation of the thermal response of PHC energy pile backfilled with phase change material. Issue 7 (October 2021) - Cao, Ziming; Zhang, Guozhu; Liu, Yiping
Abstract: The influence of phase change material (PCM) backfill material within precast high-strength concrete (PHC) pile on the thermal behavior of the energy pile is rarely studied. This paper develops a numerical model to investigate the thermal response of the PHC energy pile backfilled with PCM. The results show that the higher latent heat and thermal conductivity of PCM backfill material inside the PHC pile can effectively improve the heat transfer capacity of PHC energy pile. Besides, the intermittent operation mode is beneficial to the enhancement in heat transfer behavior of PCM-backfilled PHC energy pile. For PCM and improved PCM backfill material, the heat exchange rates of PHC energy pile at 6:18 intermittent mode rise by 57.11% and 64.06% compared with continuous mode. Finally, because the improved PCM backfill material has higher latent heat and thermal conductivity, the ground temperature around the improved PCM-backfilled PHC energy pile shows a faster growth trend than PCM backfill material. Additionally, the intermittent operation mode produces a slower growth rate of ground temperature around the pile.